Economic indicators for the Singapore economy - Neo, Peck Eng (2009)
The objective of this dissertation is to construct a composite index of leading economic indicators to predict the economic trends of the Singapore economy. It is hoped that through the use of simple statistical tools, the constructed composite index would serve as a useful model for the business community to predict the economic trend effectively and efficiently.